Social Security and Retirement during Transition:Microeconometric Evidence from Slovenia - Aleš Ahčan; Sašo Polanec (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2008)
In this paper we analyse old-age retirement decisions of Slovenian men and women eligible to retire in the period 1997-2003. In comparison to established market economies, we find relatively high hazard rates of retirement that decline with age. This peculiar pattern can be partly attributed to weak incentives to work inherent in the design of Social Security, and is reflected in predominantly negative values of accruals, and to transition-specific increase in wage inequality in the late 1980s and early 1990s. This is reflected in low wages and relativily high pensions of less productive (skilled) workers and vice versa. We also find that the probability of retirement increases with social security wealth and decreases with net wages, although the response to option value to work, when controlling for wage differences, is rather weak. Our results also imply that less educated persons, persons with greater private wealth, and persons entitled to severance payment are more likely to retire.
Keywords: J26; 330; retirement; option value; social security wealth; transition; Systemtransformation; Altersgrenze; Alterssicherung; Vermögen; Qualifikation; Lohn; Slowenien